Development of an information system at the Strategic Management Support Office of the brazilian Ministry of Health - Lunkes, Rogério João; Fey, Vladimir Arthur; Oliveira, Paulo de Tarso Ribeiro de; Campelo, Luiz Marques; Sellera, Paulo Eduardo Guedes; Curvo, Netto (Revista Cubana de Información en Ciencias de la Salud, 2015)
The development of an information system is essential for the generation of information to support the decision-making process, extending its benefits throughout the public sector especially to healthcare related organisms. To guarantee a timely government intervention, it is essential to identify problems, develop and evaluate public policy and activity, coordinate implementation, and monitor and control the provision of related services. The objective of the present study is to describe the development of a public health care information system in the Brazilian Health Ministry. In order to achieve that, a study was conducted on the development of the information system in the Strategic Management Support Office of the aforementioned Ministry. The results show that the development of an information system expands the array of relevant and reliable information through the systemic collection, integration, analysis and data presentation, which can be a key factor for the improvement of health services to the Brazilian population.